Carlisle Indian Industrial School : Indigenous histories, memories, and reclamations - Rose, Susan D., 1955-; Fear-Segal, Jacqueline (Indigenous education., 2016)
"This collection interweaves the voices of students' descendants, poets, and activists with cutting edge research by Native and non-Native scholars to reveal the complex history and enduring legacies of the school that spearheaded the federal campaign for Indian assimilation."--Provided by publisher.